A new Nabataean inscription from Taymā’ - Al-Najem, M; Macdonald, M (Wiley, 2009)
A new six-line Nabataean inscription was recently discovered during building work in the centre of the oasis city of Taymā’, north-west Saudi Arabia. It is the epitaph of a ruler, or chief citizen, of the city and is dated by the era of the Roman Province of Arabia to AD 203. All but one of the names in the text are Jewish, and this is by far the earliest record of Jews in the oasis. The Nabataean script of the epitaph is also of great interest since it shows features which are normally associated with much later periods in the development of the Nabataean into the Arabic script.